PENGARUH VARIASI BIOMASSA PISTIA STRATIOTES L. TERHADAP PENURUNAN KADAR BOD, COD, DAN TSS LIMBAH CAIR TAHU DI DUSUN KLERO SLEMAN YOGYAKARTA - Fachrurozi, M.; Utami, Listiatie Budi; Suryani, Dyah (Universitas Ahmad Dahlan, 2010)
Background: Some industries know in Orchard of direct Klero Sleman Yogyakarta throw away the liquid waste to river Gawe without done a processing beforehand, so that cause the river water becomes the impure. Others, there are sigh from society of around industry know that is incidence of smelling, so that society which live in about industry know to become annoyed. This Research aim to know influence of variation of biomassa Pistia stratiotes L. to degradation rate of BOD, COD, and TSS liquid waste know at Orchard of Klero Sleman Yogyakarta. Processing of liquid waste by exploiting Pistia stratiotes L. expected can lessen compound rate of impure toxic compound and also consisting is in underwater of waste.Method: this was pure experimental research using complete random device. Involved in variable was variation of biomassa Pistia stratiotes L. as independent variable. Rate of Biologycal Oxygen Demand (BOD), Chemical Oxygen Demand (COD), and Total Suspended Solid (TSS) as dependent variable. Research executed in Countryside of Pereng Sumberharjo Yogyakarta. Measurement of parameter BOD, COD, and TSS conducted in Laboratory Hall Technique Health of Environment (BTKL) Bantul. Sample for this research was liquid waste know in Orchard of Klero Sleman Yogyakarta. Result of research analyzed to use test of ANOVA and test of BNT (Least Significant Different).Result: Result of analysis influence variation of biomassa Pistia stratiotes L. to degradation of rate BOD, COD, and TSS use test of ANOVA show value equal to 2966,67, 8836,57, 1337,33 with level of significance equal to 0,000 (p<0,05) which indication that variation excelsior of biomassa Pistia stratiotes L. hence excelsior also degradation of rate of BOD, COD, and TSS.Conclusion: There was influences which significant between variation of biomassa Pistia stratiotes L. to degradation of rate of BOD, COD, and TSS liquid waste know in Orchard of Klero Sleman Yogyakarta.Keywords: Biomassa, Pistia Stratiotes L., BOD, COD, and TSS Liquid Wast, Soybean cake